The MEH-PPV/YAG:Ce Hybrid Nanocomposite Material for Solution Processing Fabrication of Optoelectronic Device - Chau Dinh Van (Journal of Nanomaterials, 2015)
The fabrication and the property investigation of the hybrid nanocomposite material made of poly[2-methoxy-5-(2′-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) polymer and Y3Al5O12:Ce (YAG:Ce) with the relative weight ratio of 1 : 1 in order to apply for optoelectronic devices are reported. Thermal analysis showed the hybrid material’s deterioration or decomposition when the temperature exceeded 200°C under inert gas atmosphere. Rheological measurement concluded that the material solution can be used for spinning or soft moulding lithography making large- or flexible substrate surface. Optical properties of the hybrid material are investigated. The effect of thermal treatment on the optical properties showed that, at 180°C under inert gas environment, the optical properties were enhanced. An MEH-PPV/YAG:Ce hybrid nanocomposite converted LED lamp was fabricated showing that the hybrid material is suitable as conversion material for white LED fabrication.